Research handbook on women in international management - Hutchings, Kate; Michailova, Snejina, 1965- (Cheltenham : Edward Elgar, 2014)
Research Handbook on Women in International Management is a welcome addition to the literature on international management, and a must-read for any scholar, from any country, seeking to develop theory and/or research in this field. The book is remarkable for its diversity, covering past, present and future, every region of the world, and many different types of international experience, and family circumstance.
Includes bibliographical references and index.
Keywords: Women executives; International business enterprises -- Management